Effectiveness of Anemia Prevention Education with Video Media and Leaflets on Knowledge and Attitudes of Young Women in Consuming Blood-Added Tablets at Senior High School 1 Muara Lawa - Ompusunggu, Bertaniar; Kalsum, Umi; Andraini, Rus (Rifa'Institute, 2023)
Introduction: One aspect of the cause of nutritional anemia is the lack of iron content in the food consumed every day, which is characterized by a lack of hemoglobin (Hb) levels below normal. This problem occurs because of the tendency of teenagers to have regular menstrual cycles every month and this will be exacerbated if the iron content of daily food is low. Objective: To determine the effectiveness of anemia prevention education with video media and leaflets on the knowledge and attitudes of young women in consuming blood-added tablets at SHS 1 Muara Lawa. Methods: This research is a quasi-experimental study with a two group time series pretest-posttest design which was carried out in April 2022. The population in this study were all young female students at SHS Muara Lawa, as many as 145 people. Results and Discussion: The effect of providing education on anemia prevention with video media and leaflets on the level of knowledge of young women in consuming blood-added tablets with a value of 0.00 then sig.<0.05 or (0.00<0.05) and the effect of providing education on anemia prevention with video media and leaflets on the attitude of young women in consuming blood-added tablets obtained a value of 0.00 then sig.<0.05 or (0.00<0.05). Conclusion: There is an effect of anemia prevention education with video media and leaflets on the knowledge and attitudes of young women in consuming blood-added tablets at SHS 1 Muara Lawa.